2017
DOI: 10.1186/s40816-016-0039-y
|View full text |Cite
|
Sign up to set email alerts
|

Gastrothylax crumenifer: Ultrastructure and histopathology study of in vitro trematodicidal action of Marattia fraxinea (Sm.)

Abstract: Background: Trematodicidal action of Marattia fraxinea (Sm.) rhizome, extracts against adult Gastrothylax crumenifer and its morphological changes under light and scanning electron microscope was studied in this work. This plant according to folk medicine has been reported to be used as antioxidant, antimicrobial and anthelmintic against ankylostomiasis. Methods: Preliminary screening involved the qualitative methods to detect the presence tannins, saponins, quinones, terpenoids, steroids, flavonoids, phenol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
3
4
0
Order By: Relevance
“…The present results are similar with the previous study that the researchers were observed disruptions, disarrangement, and detachment of tegument from the basal membrane, eruption, blebs, erosions and vacuoles in the tegumental structure, swelled deformed body, retracted sucker, morphological and structural changes caused by Balanites aegyptica, Plumbago indica, Dregea volubilis and the oil of Nigella sativa treated on adult Paramphistomum microbothrium, Paramphistomum cervi, Gastrothylax crumenifer, Paramphistomum explanatum and Fasciola gigantic 8,10,25,28,29 . In the present study synthetic drug albendazole also shows mild anthelminthic activity and serves few damages and vacuoles on the tegument of Cotylophoron cotylophorum.…”
Section: Discussionsupporting
confidence: 93%
“…The present results are similar with the previous study that the researchers were observed disruptions, disarrangement, and detachment of tegument from the basal membrane, eruption, blebs, erosions and vacuoles in the tegumental structure, swelled deformed body, retracted sucker, morphological and structural changes caused by Balanites aegyptica, Plumbago indica, Dregea volubilis and the oil of Nigella sativa treated on adult Paramphistomum microbothrium, Paramphistomum cervi, Gastrothylax crumenifer, Paramphistomum explanatum and Fasciola gigantic 8,10,25,28,29 . In the present study synthetic drug albendazole also shows mild anthelminthic activity and serves few damages and vacuoles on the tegument of Cotylophoron cotylophorum.…”
Section: Discussionsupporting
confidence: 93%
“…leaves ethanol extract has been proved to have phytochemical constituent that beneficial to be anthelmintic. Anthelmintic is the kind of drug which has harming effects to the helminths by affecting the vital activities, transmission of neuromuscular, ion exchange or to the tegument system that caused the helminth to be disintegrated and become paralysis or dead, therefore it will be expelled from the host's body (Nilani et al, 2012 andRajesh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[60] In vitro anthelmintic activity of plants have been studied on trematode parasites liver fluke Fasciola gigantica [61,62] tegument of G. crumenifer and on amphistome Orthocoelium scoliocoelium, F. gigantica. G. crumenifer [63][64][65][66][67] and intestinal helminthes [Table 1]. [68]…”
Section: Antibacterial Activitymentioning
confidence: 99%